Are Croatian Blood Donors Obese? - Alma Starčević; Martina Mavrinac; Nataša Katalinić; Sanja Balen (Acta Clinica Croatica, 2020)
The rising prevalence of overweight and obesity is characterized as a pandemic of the modern era. The purpose of this study was to analyze the prevalence of overweight and obesity in healthy blood donors in Primorje-Gorski Kotar County, Croatia, and the relationship between sociodemographic factors, lifestyle and eating habits, and body mass index (BMI), including the association of these factors with overweight and obesity. This cross-sectional study included 1255 healthy individuals aged between 18 and 70 years who donated blood between January 2015 and October 2016 at the Clinical Institute of Transfusion Medicine. Each participant completed a questionnaire regarding weight, height, blood type, socio-demographic factors, health parameters, physical activity, alcohol consumption, and smoking habits. Overweight was defined as BMI of 25-29.9 kg/m2, and obesity as BMI ≥30 kg/m2. A logistic regression model was used on data assessment. BMI was normal in 33.6% of participants, whereas 44.1% were overweight and 21.8% were obese. Higher BMI was correlated with male sex (odds ratio [OR]=0.21), lower education level (OR=0.77) and unhealthy diet (OR=0.57), whereas lower BMI was correlated with lower age (OR=2.05) and unemployment (OR=1.85). To our knowledge, this is the first study to investigate the prevalence of BMI in a healthy Croatian population; our results confirmed the findings of studies conducted in other European countries. Our results highlighted the importance of improving education levels and raising awareness of healthy dietary habits in high-risk groups, i.e. men and older individuals with lower education levels.